(untitled) (Agriculture Development Journal, 2024)
Access to safe food, including safe fresh produce, is essential to ensure healthy food and diets for the households and communities. However, there is limited awareness of food safety at household levels in Nepal. Food safety educational programs bridge the knowledge gap in addressing food safety. A pre- and post-assessment study was conducted during food safety trainings in five cities of Nepal to understand and evaluate the effectiveness of the trainings. Data from 102 fresh produce growers and 100 extension workers was collected through pre- and post- training responses. Questionnaires featuring 15 food safety statements were administered to the participants before and after the training. Then subsequent comparative analysis was done using the Wilcoxon signed ranks test, Mann Whitney test and Kruskal-Wallis test. The scores across subgroups: gender, age, respondent type and location were evaluated to test the significant differences. We found that the median knowledge score (indication of the knowledge or awareness level) elevated from 9.00 to 11.00 after the training. Our analysis suggested a statistically significant increase in food safety knowledge following the trainings (p<0.001). We found significant differences in the pre- and post-knowledge scores by gender (p<0.001), respondent type (p=0.005) and location (p<0.001). Our findings suggest that the targeted trainings to growers and extension workers could be an effective tool in enhancing food safety knowledge.